PERILAKU SEHAT-SAKIT MASYARAKAT DALAM PRAKTIK YOGA DI YAYASAN DHARMA STHAPANAM - Dharmayasaswini, Ni Ketut; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This study focuses on describing and analyzing deeper about healthy-sick behaviors in search of health alternatives. This research uses qualitative approach with explanative descriptive type. Health Trust theory by Rosenstrock is used. This research shows that the healthy-sick behavior of yoga practitioners at Dharma Sthapanam Foundation is motivated by health beliefs. Practitioners of hatha yoga look for health alternatives with: 1). perception of informants affected by a disease based on health condition, 2). factors of diseases that informants feel can inhibit their activities, 3). perceived benefit of practicing yoga becomes one factors of informants in practicing yoga 4). the amount of benefits felt shows that the benefits when practicing yoga is more dominant than the disadvantages so they chose to continue the practice of yoga, 5). outside factors for practicing yoga such as information about yoga on social media, magazines, even support from family, friends and so on. Key words: Healthy-sick behavior, Healt Belief Model, hatha yoga